Modelling of Output Power Response for Switched Damping Electromagnetic Energy Harvester - Ooi, B.L. (IEEE Computer Society, 2016)
The scavenging of electrical energy from surrounding environment has a number of attractions, and vibration energy is seen as one of the most potential sources. Switched damping is a method to improve the operational bandwidth of an electromagnetic energy harvester by alternatively switching the values of electrical damping coefficients of the device at different quadrants during oscillation. From the literature, a reasonably large range of resonant frequency shift can be achieved by this method, yet none of the works had demonstrated the model of the output power response. This paper presents the numerical modelling of the output power response of a damping switching device. The predictive results indicate that for a largely deviated effective loads system, significant power loss will be incurred to the output, which reduces the effectiveness of the system. Hence, this reduce the merit of the device even with a large achievable range of shifted resonant frequencies. Â© 2016 IEEE.